The Effects of Salicylic Acid and Its Derivatives on Increasing Pomegranate Fruit Quality and Bioactive Compounds at Harvest and During Storage - García-Pastor, María E.; Zapata, Pedro J.; Castillo, Salvador; Martínez-Romero, Domingo; Guillén, Fabián; Valero, Daniel; Serrano, María (Frontiers in Plant Science, 2020)
In the present research two experiments were performed to evaluate the effect of pre-harvest salicylic acid (SA), acetyl salicylic acid (ASA) and methyl salicylate (MeSa), applied as foliar spray to pomegranate ‘Mollar de Elche’, on crop yield, fruit quality parameters and bioactive compounds at harvest and during storage. In 2017 experiment, trees were treated with SA, ASA and MeSa at 1, 5 and 10 mM and higher crop yield (kg tree-1 and number of harvested fruit tree-1) and quality parameters (firmness, aril colour and individual sugars and organic acids) at harvest were obtained, as well as higher concentration in phenolics, anthocyanins and ascorbic acid. The best results were achieved with 10 mM dose of the three assayed compounds, which was chosen for 2018 experiment and results for crop yield and fruit quality attributes were confirmed. These quality traits and the concentration of phenolics, anthocyanins and ascorbic acid were maintained at higher levels in pomegranate fruit from treated trees than in controls during prolonged storage at 10 ˚C. In addition, the effects of salicylate treatments on increasing total and individual anthocyanin concentration in pomegranate arils led to aril with a deeper red colour and in turn, would be more appreciated in international market. This fact, together with the increased crop yield, would contribute to increase the profit of this crop. Thus, pre-harvest treatment with salicylates, and especially SA at 10 mM concentration, could be a safe, natural and new tool to improve fruit quality and its content on antioxidant compounds with health beneficial effects (namely, ascorbic acid, phenolics and anthocyanins) at harvest and during storage.